2022
DOI: 10.1177/11786302221091416
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, and Hygiene Service Ladders and Childhood Diarrhea in Haramaya Demographic and Health Surveillance Site, Eastern Ethiopia

Abstract: Background: The WHO/UNICEF Joint Monitoring Program (JMP) service ladders are worldwide indicators for monitoring drinking water, sanitation, and hygiene elements of the sustainable development goal targets. However, evidence on how the prevalence of childhood diarrhea looks across the service ladders is limited. This study aimed to assess the relationship between WASH service ladders and the prevalence of childhood diarrhea in Haramaya Demographic and Health Surveillance site, Eastern Ethiopia. Methods: A cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In addition, a cross-sectional study conducted in the Haramaya demographic and health surveillance site, in Eastern Ethiopia, revealed that the prevalence of diarrhea among under-five children was 24.8% (95% CI: 22.3–27.6). They highlighted that improvement of WASH service levels is needed as the prevalence of childhood diarrhea was lower in the higher service levels compared to the lower service levels ( 10 ). Moreover, a study in Northwest Ethiopia found that the great majority of the prevalence of diarrhea among under-five children is linked to households with contaminated drinking water, mainly by fecal contamination ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a cross-sectional study conducted in the Haramaya demographic and health surveillance site, in Eastern Ethiopia, revealed that the prevalence of diarrhea among under-five children was 24.8% (95% CI: 22.3–27.6). They highlighted that improvement of WASH service levels is needed as the prevalence of childhood diarrhea was lower in the higher service levels compared to the lower service levels ( 10 ). Moreover, a study in Northwest Ethiopia found that the great majority of the prevalence of diarrhea among under-five children is linked to households with contaminated drinking water, mainly by fecal contamination ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Giving fluids other than breast milk can also be a means of entry for pathogenic bacteria [10], [13]. Early childhood is very susceptible to bacteria that cause diarrhea, especially in an environment that is less hygienic and has poor sanitation [13], [14]. Exclusive breastfeeding from birth to 4 months can reduce infant and child morbidity by 10-20 times and mortality by 1-7 times [11], [12], [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…By 2020, around 2 billion people worldwide will not have access to safely managed drinking water, and 3.6 billion will not have access to safely managed sanitation services (Wagari, Girma and Geremew, 2022). In Indonesia, nearly 100 million people lack observation sheets, and compact dry to measure the microbiological quality of water.…”
Section: Methodsmentioning
confidence: 99%